(untitled) (Research, Society and Development, 2020)
Introduction: heart failure is a serious public health problem with high morbidity and mortality, with an estimated 23 million worldwide. Objective: to estimate the prevalence of priority nursing diagnoses in individuals with risk factors for heart failure in primary care. Methodology: this is a secondary analysis of a sample of 603 individuals in the Digitalis Study, for whom the priority nursing diagnoses were selected by the delphi method, 25 (twenty-five). Results: of the 603 participants, 437 were hypertensive, 380 diabetic, 180 obese and 52 with coronary artery disease, and still predominantly female and 45 to 69 years old. In addition, the significant association with sociodemographic variables, lifestyle and risk factors occurred with eleven diagnoses. Conclusion: the identification of these nursing diagnoses associated mainly with risk factors brought the perspective of planning health actions to individuals with risk factors for the development of heart failure in primary care.